#1

I'm doing a homework problem on the comp and I keep getting the same answer yet the computer says it's wrong. I checked my work and it works out fine, I don't understand what I am doing wrong.

I got -347/15 for x

Someone help me please.

```
6x+1 x-3
--------- + 9 = -------
9 4
```

I got -347/15 for x

Someone help me please.

#2

Multiply everything by 9, then 4.

oh and btw, its mathS

I'm assuming the ---------- represent a division sign

oh and btw, its mathS

I'm assuming the ---------- represent a division sign

#3

(6x+1)/9+9 =(x-3)/4

multiply both sides x4 and x9

4*(6x+1)+9*4*9 =9*(x-3)

24X+4+324 = 9x-18

15X = -346

X = -346/15

multiply both sides x4 and x9

4*(6x+1)+9*4*9 =9*(x-3)

24X+4+324 = 9x-18

15X = -346

X = -346/15

#4

my 1st rough attempt got me a -355/15

i did it in my mind tho

lemme check...whats the correct answer?

i did it in my mind tho

lemme check...whats the correct answer?

*Last edited by Aditya at Aug 29, 2008,*

#5

oh and btw, its mathS

don't start

#6

Multiply everything by 9, then 4.

oh and btw, its mathS

I'm assuming the ---------- represent a division sign

Aren't you supposed to find the LCD first, which is 36 and with that, cancel out the fractions?

#7

I got x= -352/15

#8

6x + 1 + 81 = 9/4 ( x-3)

24x + 328 = 9x - 27

15x = -355

x = -355/15 = 23 + 2/3

is what I got

24x + 328 = 9x - 27

15x = -355

x = -355/15 = 23 + 2/3

is what I got

#9

^It isn't that apparently either

Nope, I just put your answer in and the computer says it's wrong

(6x+1)/9+9 =(x-3)/4

multiply both sides x4 and x9

4*(6x+1)+9*4*9 =9*(x-3)

24X+4+324 = 9x-18

15X = -346

X = -346/15

Nope, I just put your answer in and the computer says it's wrong

*Last edited by Masamune at Aug 29, 2008,*

#10

(6x+1)/9+9 =(x-3)/4

multiply both sides x4 and x9

4*(6x+1)+9*4*9 =9*(x-3)

24X+4+324 = 9x-18

15X = -346

X = -346/15

9*3 = 27, not 18

#11

its an equal sign, you have to do the same operation on both sides.

x9 ===> 6x + 1 + 81 = 9/4x -27/4

now multiply by 4 and continue

x9 ===> 6x + 1 + 81 = 9/4x -27/4

now multiply by 4 and continue

#12

9*3 = 27, not 18

heh, engineering has made me suck at basic arithmetic

my lazy ass methods would mean "punch the thing into Mathematica" but its not installed on this computer

edit: I got myself a semesters worth of beer by doing people's homework in Mathematica

*Last edited by seljer at Aug 29, 2008,*

#13

Aren't you supposed to find the LCD first, which is 36 and with that, cancel out the fractions?

You could do that, or you can just mulitply by both numbers.

#14

6x + 1 + 81 = 9/4 ( x-3)

24x + 328 = 9x - 27

15x = -355

x = -355/15 = 23 + 2/3

is what I got

This is right

#15

Nevermind, sorry Frenchy your answer was right.

Thank you

close this if you want

Thank you

close this if you want

#16

Yeah, just plugged x = -355/15 into the original equation, it works.

#17

arghhh I got another one that I am having some trouble in.

(3n+4)(n-5)-3n(n+4)=3

I don't really need any of you guys to do this one, I just need an explanation of how I multiply (3n+4) with (n-5)

I am so horrible at math

(3n+4)(n-5)-3n(n+4)=3

I don't really need any of you guys to do this one, I just need an explanation of how I multiply (3n+4) with (n-5)

I am so horrible at math

#18

arghhh I got another one that I am having some trouble in.

(3n+4)(n-5)-3n(n+4)=3

I don't really need any of you guys to do this one, I just need an explanation of how I multiply (3n+4) with (n-5)

I am so horrible at math

You use the FOIL method.

First: 3n and n

Outside: 3n and -5

Inside: 4 and n

Last 4 and -5

#19

^Yeah I'll just expand on that a wee bit though.

You have to multiply every term of the first bracket by every term of the second bracket.

So you have (3n + 4)(n - 5)

Start with the first term in each bracket: 3n*n = n^2

Then the outer terms: 3n*(-5) = (-15n)

Then the inner terms: 4*n = 4n

Finally the last term in each bracket: 4*(-5) = -20

Then just add the terms together to get n^2 - 11n - 20

You have to multiply every term of the first bracket by every term of the second bracket.

So you have (3n + 4)(n - 5)

Start with the first term in each bracket: 3n*n = n^2

Then the outer terms: 3n*(-5) = (-15n)

Then the inner terms: 4*n = 4n

Finally the last term in each bracket: 4*(-5) = -20

Then just add the terms together to get n^2 - 11n - 20

#20

i forgot how to do math over summer. oh well i finished all my math for hs last year anyway. hehe